Cutaneous angiosarcoma: report of three different and typical cases admitted in a unique dermatology clinic - Aline Neves Freitas Cabral; Rafael Henrique Rocha; Ana Cristina Vervloet do Amaral; Karina Bittencourt Medeiros; Paulo Sérgio Emerich Nogueira; Lucia Martins Diniz (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Angiosarcoma is a rare and aggressive tumor with high rates of metastasis and relapse. It shows a particular predilection for the skin and superficial soft tissues. We report three distinct and typical cases of angiosarcoma that were diagnosed in a single dermatology clinic over the course of less than a year: i) Angiosarcoma in lower limb affected by chronic lymphedema, featuring Stewart-Treves syndrome; ii) a case of the most common type of angiosarcoma loated in the scalp and face of elderly man and; iii) a skin Angiosarcoma in previously irradiated breast. All lesions presented characteristic histopathological findings: irregular vascular proliferation that dissects the collagen bundles with atypical endothelial nuclei projection toward the lumen.